The Role of Noninvasive Ventilation in the Hospital and Outpatient Management of Chronic Obstructive Pulmonary Disease - Hoo, Guy W. Soo (Seminars in Respiratory and Critical Care Medicine, 2015)
Positive pressure noninvasive ventilation (NIV) has become widely accepted in the treatment of both hospitalized and outpatient subjects with chronic obstructive pulmonary disease (COPD). The support has evolved over the past two decades to be part of first-line management in acute exacerbations of COPD and is also instrumental in discontinuing mechanical ventilation in COPD patients with acute respiratory failure. It is also suitable for treatment of COPD with other associated conditions including pneumonia, following lung resectional surgery, with concomitant obstructive sleep apnea and as part of end-of-life care. Short-term application can also facilitate some endoscopic procedures that may otherwise require endotracheal intubation. Outpatient use of NIV in COPD has garnered much attention, but the support has not been as robust as with NIV in hospitalized patients. However, an approach with higher pressures with a goal of significant reduction in daytime PaCO2 may be an effective strategy. NIV can also facilitate exercise training in pulmonary rehabilitation. A portable device which can augment tidal volume during ambulation and other activities of daily living may further expand the use of NIV in COPD patients.
Keywords: COPD; noninvasive ventilation; hypercapnia; chronic respiratory failure